Evidence for charge transfer from hydrogen molecular ions to copper atoms in a neon–hydrogen analytical glow discharge. Issue 11 (13th September 2016) - Mushtaq, Sohail; Steers, Edward B. M.; Hoffmann, Volker; Weiss, Zdeněk; Pickering, Juliet C.
Abstract : We show initial evidence that analyte atoms can be ionized by asymmetric charge transfer (ACT) process involving molecular ions, (M2+-ACT) in analytical glow discharges. Abstract : Extensive investigations have been carried out in recent years on the effects of the presence of small amounts of molecular gases in analytical glow discharges (GDs) using argon as the plasma gas. Complementary studies using neon have shown that, when hydrogen is added to a neon discharge with a copper sample, the intensities of lines from most of the upper energy levels in the Cu II 3d 9 ( 2 D)4p sub-configuration decrease. However, the 224.700 nm spectral line and other lines from the same upper level ( 3 Po2) increase in intensity and this effect cannot be produced by the excitation processes normally considered. We show that asymmetric charge transfer (ACT) excitation by hydrogen molecules (H2 -ACT) is the most likely explanation, the first time this process has been reported for any element in analytical GDs. We also explain why a similar effect is not observed with added nitrogen, although the ionization energies of hydrogen and nitrogen molecules are very similar.